A cladding modified optical fiber and a method for manufacturing the same

CN123003139APending Publication Date: 2026-10-30WUHAN CHANGJIN PHOTONICS TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611413304.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-11
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]本发明的目的在于,提供一种包层改性光纤及其制备方法,用于改善现有高掺杂光纤因纤芯掺杂浓度过高,导致纤芯折射率偏大、光纤色散特性差、传输损耗高且工艺稳定性不足的技术问题

Benefits of technology

[0033]本发明的有益效果是:区别于现有技术的情况,本发明提供一种包层改性光纤及其制备方法,上述包层改性光纤通过在纤芯外侧设置高热膨胀系数材质的应力层,利用应力层与纯石英基体之间显著的热膨胀系数差异,在光纤拉制后的极速冷却过程中使应力层急剧收缩而石英基体体积基本不变,二者收缩量不匹配从而对纤芯施加径向拉应力,经光弹效应使纤芯折射率降低,增大纤芯与包层的相对折射率差,增强光模约束、降低弯曲损耗,最终提升激光器的输出功率与光束质量;上述制备方法基于MCVD工艺,经含氟阻挡层沉积、疏松层沉积、玻璃化烧缩、芯棒加工引入应力层及高温拉丝即可制得,应力在拉丝极速冷却阶段自然形成,无需额外热处理,工艺简便且兼容性好。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003139A_ABST
    Figure CN123003139A_ABST
Patent Text Reader

Abstract

The application provides a cladding modified optical fiber and a preparation method thereof. The cladding modified optical fiber is prepared by arranging a stress layer of a material with a high thermal expansion coefficient outside a fiber core. When the stress layer sharply shrinks and the quartz base volume basically does not change during rapid cooling after drawing, the shrinkage of the stress layer and the quartz base is not matched, so that a radial tensile stress is applied to the fiber core, the refractive index of the fiber core is reduced through the photoelastic effect, the relative refractive index difference between the fiber core and the cladding is increased, the light mode is constrained, the bending loss is reduced, and finally the output power and the beam quality of a laser are improved. The preparation method is based on the MCVD process, the stress layer is introduced through barrier layer deposition, loose layer deposition, vitrification and shrinkage, and rod processing and drawing, and the stress is naturally formed during the cooling stage of drawing, so that additional heat treatment is not needed, and the process is simple and has good compatibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of gain fiber technology, and in particular to a cladding modified fiber and its preparation method. Background Technology

[0002] Fiber lasers and fiber amplifiers are core light sources in fields such as industrial precision machining, lidar, medical surgery, atmospheric remote sensing, and space laser communication. Highly rare-earth-doped active fibers (ytterbium-doped Yb, erbium-doped Er, thulium-doped Tm, etc.) are the core of their gain media. The low-brightness, poorly directional pump light output from the pump source is converted into high-brightness, highly directional laser light through the gain medium. To achieve effective gain, shorten fiber length, improve pump absorption efficiency, suppress ion quenching, and realize compact laser design, the industry generally adopts a high-concentration rare-earth doping scheme, that is, significantly increasing the Yb³ content in the fiber core. + Tm³ + The molar concentration of plasma doping significantly improves the gain per unit length, thus making it suitable for cutting-edge applications such as kilowatt-level continuous lasers, pulsed ultrashort lasers, and thulium-doped lasers in the 2μm eye-safe band.

[0003] However, high doping concentrations lead to an excessively high refractive index in the fiber core, increasing the refractive index difference between the core and cladding, which in turn excites a large number of higher-order transmission modes, degrading the quality of the laser output beam. Simultaneously, an excessively high refractive index compresses the effective mode field area, lowers the threshold for nonlinear effects such as stimulated Raman scattering and stimulated Brillouin scattering, and exacerbates bending loss and fiber splice mismatch loss, including end-face feedback and splice diffusion problems. These drawbacks severely limit the engineering application of highly doped active fibers in high-power fiber lasers.

[0004] To address the aforementioned issues, existing technologies employ fluorine (F) doping to reduce the refractive index of the fiber core. However, with the ever-increasing performance requirements for highly doped rare-earth optical fibers, the ability of F to reduce the refractive index is limited and cannot support higher concentrations of rare-earth doping. Therefore, there is an urgent need to reduce the refractive index of the fiber core through new technological means. Summary of the Invention

[0005] The purpose of this invention is to provide a cladding-modified optical fiber and its preparation method, which can improve the technical problems of existing highly doped optical fibers, such as excessive core refractive index, poor fiber dispersion characteristics, high transmission loss and insufficient process stability due to excessive core doping concentration.

[0006] To solve the above-mentioned technical problems, the technical solution provided by the present invention is as follows: In a first aspect, the present invention provides a cladding-modified optical fiber, comprising a core and a cladding arranged radially from the inside to the outside, wherein the refractive index of the core is greater than that of the cladding. The cladding modified fiber also includes a stress layer disposed radially on the outside of the fiber core, which is used to reduce the refractive index of the fiber core by generating stress.

[0007] Specifically, the aforementioned cladding-modified optical fiber has a stress layer made of a material with a high coefficient of thermal expansion on the outside of the fiber core. During the rapid cooling process after the fiber is drawn, the stress layer shrinks rapidly due to its high coefficient of thermal expansion, while the pure silica matrix of the fiber core and cladding remains essentially unchanged in volume due to its extremely low coefficient of thermal expansion. Because of the mismatch in the amount of shrinkage, the stress layer applies radial tensile stress to the silica matrix and conducts it to the fiber core. This stress further reduces the refractive index of the fiber core through the photoelastic effect, thereby increasing the relative refractive index difference between the fiber core and the cladding, enhancing optical mode confinement, suppressing bending loss and mode leakage, and ultimately improving the output power and beam quality of the laser prepared from this optical fiber.

[0008] Preferably, the stress layer is centrally symmetrical about the central axis of the fiber core, so that the reduction in refractive index in all directions is consistent; and / or, the relative refractive index difference between the stress layer and the cladding is -0.5% to +0.5%; wherein, the relative refractive index difference Δn is a dimensionless parameter that measures the degree of difference in refractive index between two media, and is usually defined in the field of optical fiber as: Δn=(n1-n2) / n1×100%, where n1 is the refractive index of the layer being compared (here, the stress layer) and n2 is the refractive index of the reference layer (here, the cladding).

[0009] Specifically, by making the stress layer centrally symmetrical about the fiber core's central axis, the tensile stress applied by the stress layer to the fiber core during cooling and shrinkage can be ensured to be uniform in all circumferential directions. This ensures that the reduction in refractive index in all directions of the fiber core remains consistent, avoiding refractive index anisotropy caused by uneven stress distribution. This effectively suppresses birefringence and polarization-related losses, and maintains the circular symmetry and polarization stability of the beam cross-section.

[0010] Specifically, limiting the relative refractive index difference between the stress layer and the cladding to the range of -0.5% to +0.5% can prevent the formation of additional waveguides at the stress layer and interference with the main mode transmission due to an excessively large refractive index difference, while also avoiding the limitation of the selection space for stress layer materials and the stress control effect due to an excessively small refractive index difference.

[0011] Preferably, the stress layer is a continuous annular structure that completely encloses the fiber core, or it is a plurality of stress units that are spaced apart circumferentially on the outside of the fiber core. When the stress layer is a continuous ring structure, the continuous ring structure is set on the outer surface side of the fiber core or the outer surface side of the cladding; when the stress layer consists of multiple stress units, the multiple stress units are embedded in the radial center of the cladding.

[0012] Specifically, the continuous ring structure completely encloses the fiber core, which can continuously and uniformly apply tensile stress along the circumference, ensuring that the refractive index of the fiber core decreases in a consistent manner in all directions. The sleeve form facilitates tight fitting and has high stress transmission efficiency. Multiple stress units are distributed at intervals along the circumference. The stress of each stress unit can still form a uniform circumferential effect on the fiber core after the stress is superimposed. Furthermore, the embedded arrangement in the radial center of the cladding can keep the stress material at an appropriate distance from the fiber core, avoiding direct contact that interferes with the doping distribution. At the same time, the stress magnitude can be flexibly controlled by adjusting the number, diameter, and material of the stress units.

[0013] Preferably, when the stress layer is disposed on the outer surface side of the fiber core and the numerical aperture of the fiber core is ≥0.10, the stress layer is formed of a first stress material; when the stress layer is disposed on the outer surface side of the fiber core and the numerical aperture of the fiber core is <0.10, the stress layer is formed of a second stress material; when the stress layer is disposed in the radial center of the cladding or on the outer surface side of the cladding, the stress layer is formed of a first stress material. Among them, the relative refractive index difference between the first stress material and the cladding is negative, and its coefficient of thermal expansion is greater than that of the cladding; the relative refractive index difference between the second stress material and the cladding is positive, and its coefficient of thermal expansion is greater than that of the cladding.

[0014] Specifically, when the stress layer is located on the outer surface of the fiber core and the numerical aperture of the fiber core is ≥0.10, a first stress material with a negative relative refractive index difference is used. This can utilize its high thermal expansion coefficient to generate tensile stress to reduce the refractive index of the fiber core, while preventing the positive refractive index material close to the fiber core from further increasing the numerical aperture of the fiber core, thereby preventing the multimode transmission and beam quality degradation caused by an excessively large numerical aperture. When the stress layer is located on the outer surface of the fiber core and the numerical aperture of the fiber core is <0.10, a second stress material with a positive relative refractive index difference is used. This can apply tensile stress to reduce the refractive index of the fiber core, while using the positive refractive index difference of the stress layer itself to form an auxiliary constraint on the fiber core, compensating for the decrease in numerical aperture caused by stress, and preventing insufficient constraint capability of low numerical aperture fibers. When the stress layer is located in the radial middle or outer surface of the cladding, since it is far from the waveguide region of the fiber core, using a first stress material with a negative relative refractive index difference can avoid the formation of additional waveguide interference in the main mode transmission, while fully utilizing its stress modulation effect of high thermal expansion coefficient.

[0015] Preferably, the core diameter is 4 to 100 μm; and / or, the material of the stress layer includes at least one of B2O3, TiO2 and alkali metal oxides; and / or, the absolute refractive index of the core is reduced by not less than 0.0003 compared to the absolute refractive index of the core without a stress layer.

[0016] Specifically, the aforementioned core diameter range ensures both single-mode transmission and high beam quality under small core diameters, while also meeting the high power carrying capacity requirements under large core diameters, thus adapting to laser applications with different power levels and beam quality requirements. The aforementioned stress layer materials all have a significantly higher coefficient of thermal expansion than pure silica, which can generate sufficient tensile stress during rapid cooling. They also have good chemical compatibility and process maturity with the silica matrix, and can be stably deposited using conventional fiber preform fabrication processes. Furthermore, controlling the reduction in the absolute refractive index of the core to be no less than 0.0003 ensures that the photoelastic effect induced by the stress layer achieves a practically meaningful control over the refractive index of the core, making the increase in the relative refractive index difference between the core and cladding and the improvement in optical mode confinement capabilities have perceptible technical effects.

[0017] Secondly, the present invention also provides a method for preparing the above-mentioned cladding modified optical fiber, characterized in that it includes: S10, a clean quartz tube is placed on a lathe, a first mixed gas is introduced into the quartz tube, and a fluorine-containing barrier layer is deposited on the inner wall of the quartz tube to obtain a first reaction tube; the first mixed gas includes oxygen, silicon tetrachloride and sulfur hexafluoride. S20, a second mixed gas is introduced into the first reaction tube, and a loose layer is deposited on the wall of the first reaction tube to obtain the second reaction tube; the second mixed gas includes oxygen, helium, silicon tetrachloride and germanium tetrachloride; S30, the second reaction tube is vitrified and scalded at 1800-2100℃ to form a solid rod, thus obtaining the fiber core preform rod; S40, the core preform is processed into a core rod to form a stress layer at any of the following locations: the outer surface of the core, the radial center of the cladding, or the outer surface of the cladding, to obtain a cladding modified preform. S50, the cladding-modified preform is subjected to high-temperature melting and drawing at 2000-2200℃ to obtain the cladding-modified optical fiber.

[0018] Specifically, the fluorine-containing barrier layer formed in step S10 effectively inhibits the outward diffusion of subsequent core dopants, ensuring the accuracy and stability of the core refractive index distribution. Simultaneously, it acts as a corrosion barrier layer to protect the quartz tube substrate, improving the reliability and yield of the deposition process. The germanium-containing porous layer deposited in step S20 increases the core refractive index while forming a porous structure, facilitating the full removal of impurities and uniform doping distribution during subsequent glassization. The introduction of helium further promotes uniform deposition temperature, improving layer thickness and compositional consistency. The glassization shrinkage in step S30 at 1800–2100℃ allows the porous layer to be fully sintered and densified, removing porosity and residual impurities, while also preventing excessively high temperatures from causing germanium and other dopants to precipitate. The process involves element volatilization to obtain a dense core preform with excellent optical uniformity. Step S40 introduces a stress layer through core processing, allowing for flexible selection of the stress layer's location based on different application requirements, thus offering high design freedom and process adaptability. Step S50, with high-temperature drawing at 2000–2200℃, ensures the preform fully melts and stably forms fibers. Simultaneously, the rapid cooling during the drawing process causes the high thermal expansion coefficient stress layer to naturally shrink and induce radial tensile stress. This eliminates the need for additional heat treatment steps, enabling stable control of the core refractive index. Ultimately, this yields cladding-modified optical fibers with low bending loss, strong optical mode constraint, and high beam quality. The overall process is based on the mature MCVD (Modified Chemical Vapor Deposition) route, offering good equipment compatibility, clear parameter windows, and high batch consistency.

[0019] Preferably, after step S20 and before step S30, the following steps are further included: The second reaction tube is immersed in the first ion solution containing rare earth ions; The second reaction tube, after soaking, is baked under a third mixed gas to obtain a first dry reaction tube; the third mixed gas includes silicon tetrachloride, oxygen, helium and chlorine.

[0020] Specifically, the addition of rare earth soaking and baking steps allows the porous structure of the loose layer to adsorb the solution containing rare earth ions, achieving uniform and high-concentration doping of rare earth ions in the fiber core. This overcomes the bottleneck of poor volatility of rare earth halides and the difficulty in achieving efficient doping through conventional vapor deposition. Furthermore, the doping amount can be precisely controlled by the solution concentration and soaking time, making it suitable for Er 3+ Yb 3 + Various rare earth ions are present; subsequently, it is baked in a mixed atmosphere containing silicon tetrachloride, oxygen, helium, and chlorine, where chlorine removes moisture and hydroxyl groups from the porous layer, preventing OH-. -In the near-infrared band, where absorption loss is high, silicon tetrachloride can replenish the silicon source and fill the pores to promote subsequent densification. Oxygen and helium maintain the oxidation atmosphere and temperature uniformity, respectively, so that rare earth ions are stably fixed and fully dried. Finally, under the premise of being compatible with MCVD process, an active gain fiber with uniform rare earth doping, low hydroxyl content and low optical loss is obtained (if there is no rare earth soaking and baking step, a passive fiber is prepared).

[0021] Preferably, the solvent of the first ionic solution is pure water or anhydrous ethanol, the solute contains at least one rare earth ion with a rare earth ion concentration of 0.03–0.2 mol / L, and the soaking time is 0.5–2 h; and / or, In the third gas mixture, the flow rate of silicon tetrachloride is greater than 180 sccm and less than or equal to 300 sccm, and the flow rate of chlorine is greater than 100 sccm and less than or equal to 200 sccm; and / or, The second reaction tube is baked using an oxyhydrogen lamp at a temperature of 800–1400°C (or 800–1300°C). The oxyhydrogen lamp is moved in the same direction as the flow of the third mixed gas in the second reaction tube.

[0022] Specifically, by synergistically optimizing the solvent system, doping concentration, and soaking time of the rare earth ion solution, it is possible to ensure that rare earth ions are fully and uniformly diffused and adsorbed in the porous structure of the loose layer, avoiding insufficient doping due to insufficient adsorption or ion agglomeration due to excessive concentration, while taking into account both doping effect and process efficiency.

[0023] Specifically, by rationally controlling the flow ratio of silicon source and chlorine in the reaction gas, it is possible to ensure that the pores of the loose layer are fully filled and create conditions for subsequent glass densification, while achieving complete removal of hydroxyl groups and moisture, significantly reducing the intrinsic absorption loss of the optical fiber, and avoiding waste of raw materials or corrosion of the pipe wall caused by gas flow imbalance.

[0024] Specifically, by matching the design of the baking heat source, temperature range, and heat source movement method, the heating area and the front edge of the reaction gas can be synchronously advanced along the optical fiber axis, ensuring that the dehydration, oxidation, and ion fixation processes are carried out uniformly and fully in the axis, avoiding local overheating or reaction lag, and finally obtaining an active cladding modified optical fiber with uniform rare earth doping, low hydroxyl content, good axial consistency, and low optical loss.

[0025] Preferably, step S40 specifically includes: removing the cladding and taking out the fiber core, sequentially matching the first stress-modifying component and the first quartz sleeve according to a preset core-cladding ratio, and sequentially performing high-temperature melting and shrinking at 2000-2100℃; or, The dimensions of the fiber core preform are tested. The second quartz sleeve is matched according to the preset core-to-pack ratio and shrunk at high temperature of 2000-2100℃. The shrunk first rod is inserted into the third quartz sleeve. Holes are drilled on the third quartz sleeve at positions symmetrical to the center of the fiber core, and at least two second stress-modifying components are inserted and shrunk at high temperature of 2000-2100℃. Alternatively, the core preform is dimensionally tested, a fourth quartz sleeve is matched according to the preset core-to-wall ratio, and the core is melted and shrunk at a high temperature of 2000-2100℃. The shrunk second rod is then fitted into the second stress-modified component.

[0026] Specifically, the scheme of matching and shrinking the first stress-modifying component with the first quartz sleeve allows the first stress-modifying component to be closely attached to the fiber core, resulting in the shortest tensile stress transmission path, the most direct refractive index control, and precise control of the core-to-cladding ratio. The scheme of combining the second quartz sleeve, the third quartz sleeve, and the second stress-modifying component allows the second stress-modifying component to be positioned in the radial center of the cladding, ensuring uniform circumferential stress distribution while maintaining an appropriate distance from the fiber core, avoiding direct interference with the doped area of ​​the fiber core, and achieving high positioning accuracy. The scheme of combining the fourth quartz sleeve with the second stress-modifying component allows the second stress-modifying component to be placed on the outermost side of the cladding, which is the simplest process, causes minimal disturbance to the internal structure, and facilitates subsequent coating protection.

[0027] Preferably, the first stress-modifying component is a TiO2 sleeve with a refractive index lower than that of the fiber core; and / or, the second stress-modifying component is a boron rod or a B2O3 sleeve, wherein the molar concentration of B2O3 in the boron rod is 10 mol% to 30 mol.

[0028] Specifically, the first stress-modifying component uses a TiO2 sleeve, which generates strong radial tensile stress during rapid cooling due to its high coefficient of thermal expansion. Its refractive index is lower than that of the fiber core, which avoids the formation of additional waveguides. The sleeve structure also facilitates a tight fit with the core rod. The second stress-modifying component uses a boron rod or a B2O3 sleeve. The coefficient of thermal expansion of B2O3 is much higher than that of quartz, resulting in a significant shrinkage effect. The boron rod and B2O3 sleeve forms are respectively adapted to the stress layer layout inside and outside the cladding. The molar concentration of B2O3 in the boron rod is limited to 10 mol% to 30 mol%, which can ensure effective tensile stress while avoiding excessive concentration that may cause difficulties in glassization or crystallization. Thus, efficient and controllable stress regulation can be achieved under the premise of stable process.

[0029] Preferably, in step S10: the quartz tube is baked using an oxyhydrogen lamp at a temperature of 1400–2100°C, and the moving direction of the oxyhydrogen lamp is the same as the flow direction of the first mixed gas inside the quartz tube; and / or, the flow rate of sulfur hexafluoride in the first mixed gas is greater than 0 and less than or equal to 50 sccm, and the flow rate of silicon tetrachloride is greater than 100 sccm and less than 300 sccm.

[0030] Specifically, the hydrogen-oxygen lamp is heated at 1400–2100°C and moves in the same direction as the flow of the first mixed gas. This allows the heating area and the front of the reaction gas to advance synchronously along the axial direction, ensuring a uniform and sufficient deposition reaction. This avoids local overheating that could lead to fluorine volatilization or deformation of the quartz tube, while also preventing the deposition layer from becoming loose and lacking adhesion due to excessively low temperatures. The flow rate of sulfur hexafluoride in the first mixed gas is greater than 0 and ≤50 sccm, and the flow rate of silicon tetrachloride is greater than 100 sccm and <300 sccm. This ensures sufficient fluorine doping to form a low-refractive-index fluorine-containing barrier layer and inhibits the outward diffusion of subsequent core dopants. It also avoids excessively high fluorine flow rates that could lead to excessively low refractive indices, loose layer structures, or excessive corrosion. At the same time, the silicon tetrachloride flow rate range ensures a reasonable deposition rate and uniform layer thickness, thereby obtaining a fluorine-containing barrier layer with uniform composition, dense structure, and precisely controllable refractive index.

[0031] Preferably, in step S20: the first reaction tube is baked using an oxyhydrogen lamp at a temperature of 1400–2100°C, and the direction of movement of the oxyhydrogen lamp is the same as the direction of flow of the second mixed gas in the first reaction tube; and / or, the flow rate of silicon tetrachloride in the second mixed gas is greater than 150 sccm and less than or equal to 300 sccm, and the flow rate of germanium tetrachloride is greater than 5 sccm and less than or equal to 30 sccm.

[0032] Specifically, the hydrogen-oxygen lamp is heated at 1400–2100°C and moves in the same direction as the flow of the second mixed gas. This allows the heating area and the front of the reaction gas to advance synchronously along the axial direction, ensuring uniform thickness and composition of the loose layer. At the same time, it avoids insufficient deposition due to excessively low temperature or premature vitrification of the loose layer due to excessively high temperature, thus losing its porous structure. This preserves sufficient adsorption pores for subsequent rare earth ion doping. In the second mixed gas, the flow rate of silicon tetrachloride is greater than 150 sccm and ≤300 sccm, and the flow rate of germanium tetrachloride is greater than 5 sccm and ≤30 sccm. The flow rate of silicon tetrachloride ensures a reasonable deposition rate and loose layer thickness, while the flow rate of germanium tetrachloride precisely controls the amount of germanium doping in the fiber core and the increase in refractive index. This avoids insufficient germanium doping leading to a small numerical aperture and weak optical mode confinement, while excessive germanium doping prevents excessive numerical aperture, multimode transmission, or germanium volatilization loss. As a result, a germanium-containing loose layer with uniform thickness, good porous structure, and precise controllable germanium doping is obtained.

[0033] The beneficial effects of this invention are as follows: Unlike existing technologies, this invention provides a cladding-modified optical fiber and its preparation method. The cladding-modified optical fiber uses a stress layer made of a material with a high coefficient of thermal expansion on the outside of the fiber core. Utilizing the significant difference in the coefficient of thermal expansion between the stress layer and the pure silica matrix, the stress layer contracts rapidly during the rapid cooling process after fiber drawing, while the volume of the silica matrix remains essentially unchanged. This mismatch in contraction applies radial tensile stress to the fiber core, reducing the refractive index of the core through photoelasticity, increasing the relative refractive index difference between the core and cladding, enhancing optical mode constraint, reducing bending loss, and ultimately improving the output power and beam quality of the laser. The preparation method is based on the MCVD process, which involves the deposition of a fluorine-containing barrier layer, deposition of a porous layer, glass transition shrinkage, core rod processing to introduce the stress layer, and high-temperature drawing. The stress is naturally formed during the rapid cooling stage of drawing, requiring no additional heat treatment. The process is simple and has good compatibility. Attached Figure Description

[0034] Figure 1 This is a schematic diagram of the end face structure of the ytterbium-doped cladding modified optical fiber provided in Embodiment 1. Figure 2 This is a schematic diagram of the end face structure of the ytterbium-doped cladding modified optical fiber provided in Embodiment 2. Figure 3 This is a schematic diagram of the end face structure of the ytterbium-doped cladding modified optical fiber provided in Embodiment 3. Figure 4 A schematic diagram of the end face structure of a ytterbium-doped ordinary optical fiber provided for Comparative Example 1; In the attached diagram: 10 – fiber core; 20 – cladding; 30 – stress layer; 31 – stress element. Detailed Implementation

[0035] The technical solutions in this embodiment will be clearly and completely described below with reference to this embodiment. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0036] Existing technologies typically employ fluorine doping to reduce the refractive index of optical fibers, thereby increasing the relative refractive index difference between the core and cladding. However, the amount of fluorine doping is limited by the solid solubility of quartz glass, and once this limit is reached, the refractive index cannot be further reduced, thus hindering improvements in the numerical aperture and bending resistance of the optical fiber. This invention proposes a technique for controlling the refractive index of the fiber core based on stress effects. By setting a stress layer with a high coefficient of thermal expansion on the outside of the fiber core, radial tensile stress is generated during rapid cooling due to the difference in thermal expansion coefficients between the stress layer and the quartz matrix. This stress is then reduced through photoelastic effects, thereby breaking through the fluorine doping limit bottleneck, further increasing the relative refractive index difference, reducing bending loss, and improving laser performance.

[0037] The main principle of this invention is based on the difference in thermal expansion coefficients between different materials. A controllable tensile stress is induced in the fiber core through a rapid cooling process after high-temperature drawing, thereby reducing the refractive index of the fiber core using the photoelastic effect. Specifically: During high-temperature drawing, the optical fiber is in a molten state with no residual stress, and the refractive index of each part remains intrinsic. Upon entering the rapid cooling stage, the stress layer material with a high thermal expansion coefficient contracts rapidly with decreasing temperature, significantly reducing its volume. Meanwhile, the pure quartz matrix, with its extremely low thermal expansion coefficient, maintains a relatively constant volume. This mismatch in contraction causes the stress layer to generate continuous radial tensile stress on the quartz matrix, which is then transmitted to the fiber core. According to the photoelastic effect, the refractive index of the fiber core further decreases under tensile stress, thereby increasing the relative refractive index difference between the fiber core and the cladding, enhancing optical mode constraint, reducing bending loss, and ultimately improving the output power and beam quality of the laser.

[0038] The technical solution of the present invention will now be described in conjunction with specific embodiments.

[0039] Example 1: Please see Figure 1 This embodiment provides a ytterbium-doped cladding modified optical fiber, comprising a core 10 and a cladding 20 arranged radially from the inside to the outside. The refractive index of the core 10 is greater than that of the cladding 20, and the core 10 is Yb-doped. 3+ The quartz glass cladding 20 is primarily composed of pure quartz glass. The ytterbium-doped cladding modified optical fiber also includes a stress layer 30 disposed on the outside of the fiber core 10. The stress layer 30 is used to reduce the refractive index of the fiber core 10 by generating stress. In this embodiment 1, the stress layer 30 is a continuous annular structure that completely encloses the fiber core 10 and is disposed close to the outer surface of the fiber core 10. Figure 1 As shown.

[0040] In Example 1, the stress layer 30 is centrally symmetrical about the central axis of the fiber core 10, so that the refractive index reduction in all directions of the fiber core 10 is consistent, thereby avoiding refractive index anisotropy caused by uneven stress distribution and suppressing birefringence and polarization-related losses.

[0041] In Example 1, the relative refractive index difference between the stress layer 30 and the cladding 20 is -0.2%. The diameter of the fiber core 10 is 10 μm, and the material of the stress layer 30 is TiO2, whose coefficient of thermal expansion is significantly higher than that of pure quartz.

[0042] Specifically, the ytterbium-doped cladding modified optical fiber provided in Example 1 is prepared through the following steps: Step (1): Place a clean quartz tube on a lathe, introduce a first mixed gas into the quartz tube, and simultaneously bake the quartz tube using an oxyhydrogen lamp at a temperature of 1800℃. The direction of movement of the oxyhydrogen lamp is the same as the flow direction of the first mixed gas inside the quartz tube. A fluorine-containing barrier layer is deposited on the inner wall of the quartz tube to obtain the first reaction tube. The first mixed gas includes oxygen, silicon tetrachloride, and sulfur hexafluoride, wherein the flow rate of sulfur hexafluoride is 20 sccm and the flow rate of silicon tetrachloride is 200 sccm.

[0043] Step (2): A second mixed gas is introduced into the first reaction tube, and the first reaction tube is baked using an oxyhydrogen lamp at a temperature of 1800°C. The moving direction of the oxyhydrogen lamp is the same as the flow direction of the second mixed gas in the first reaction tube. A loose layer is deposited on the wall of the first reaction tube to obtain the second reaction tube. The second mixed gas includes oxygen, helium, silicon tetrachloride, and germanium tetrachloride; wherein the flow rate of silicon tetrachloride is 200 sccm, and the flow rate of germanium tetrachloride is 15 sccm.

[0044] Step (3): Immerse the second reaction tube in a solution containing Yb 3+ In the first ion solution, the solvent is pure water, and the solute is YbCl3, Yb 3+ The concentration was 0.1 mol / L, the soaking time was 1 h, and the Yb-containing compounds were adsorbed by utilizing the porous structure of the loose layer. 3+ The solution to achieve Yb 3+ Uniform adsorption in the loose layer.

[0045] Step (4): The soaked second reaction tube is placed under a third mixed gas for baking. A hydrogen-oxygen lamp is used for baking at 1100℃. The moving direction of the hydrogen-oxygen lamp is the same as the flow direction of the third mixed gas in the second reaction tube, resulting in a first dry reaction tube. The third mixed gas includes silicon tetrachloride, oxygen, helium, and chlorine, with a silicon tetrachloride flow rate of 250 sccm and a chlorine flow rate of 150 sccm. Baking under a chlorine-containing mixed atmosphere removes moisture and hydroxyl groups from the loose layer, preventing OH-. - Strong absorption loss occurs in the near-infrared band. Silicon tetrachloride replenishes the silicon source and fills the pores to promote subsequent densification.

[0046] Step (5): The first drying reaction tube is vitrified and shrunk at 1950℃ to form a solid rod, thus obtaining the fiber core preform.

[0047] Step (6), core rod processing of the fiber core preform: first, the rod is hollowed out, and the Yb-doped core is removed. 3+The core preform (2 mm in diameter) is removed from the cladding 20, and then, with a core-to-cladding ratio of 0.08, it is matched with a high-purity TiO2 sleeve and melt-shrunk at 2050℃ to form a sleeve rod with an outer diameter of 10 mm. Then, with a core-to-cladding ratio of 0.08, it is matched with a high-purity quartz sleeve and melt-shrunk at 2050℃ to form a sleeve rod with an outer diameter of 35 mm, thus obtaining the cladding modified preform. The refractive index of the TiO2 sleeve is lower than that of the core 10.

[0048] Step (7): The cladding modified preform is subjected to high-temperature melting and drawing at 2100℃ to obtain the cladding modified optical fiber.

[0049] Example 2: Please see Figure 2 This embodiment 2 provides a ytterbium-doped cladding modified optical fiber, whose structure is basically the same as that of embodiment 1, and the fiber core 10 is also Yb-doped. 3+ The difference between this and other quartz glass is that the stress layer 30 consists of multiple stress units 31 spaced circumferentially on the outer side of the fiber core 10, with the stress units 31 embedded in the radial center of the cladding 20. In this embodiment 2, there are 8 stress units 31, evenly distributed circumferentially. The stress units 31 are made of boron rods, with a B2O3 molar concentration of 20 mol%.

[0050] The preparation method of Example 2 is basically the same as that of Example 1, except for step (6): the fiber core diameter and outer diameter of the fiber preform are tested, and the core diameter and outer diameter are 2mm and 15mm respectively; then, according to the core-to-cladding ratio of 0.08, it is matched with a high-purity quartz sleeve and shrunk at 2050℃ to form a sleeve rod with an outer diameter of 35mm; the shrunk sleeve rod is inserted into the pure quartz sleeve, and then the assembled pure quartz sleeve is punched with holes. The punching positions are symmetrical with the fiber core, and the number of holes is 8. A boron rod (the molar concentration of B2O3 in the boron rod is 20mol%) is inserted, and the rod is shrunk to obtain the cladding modified preform. The remaining steps and process parameters are the same as those in Example 1.

[0051] Example 3: Please see Figure 3 This embodiment 3 provides a ytterbium-doped cladding modified optical fiber, whose structure is basically the same as that of embodiment 1, and the fiber core 10 is also Yb-doped. 3+ The difference between this and other quartz glass is that the stress layer 30 has a continuous annular structure and is disposed on the outer surface of the cladding 20. The material of the stress layer 30 is B2O3.

[0052] The preparation method of this embodiment 3 is basically the same as that of embodiment 1, except for step (6): the fiber core diameter and outer diameter of the fiber preform are tested, and the fiber core diameter and outer diameter are 2mm and 15mm respectively; then, according to the core-cladding ratio of 0.08, it is matched with a high-purity quartz sleeve and melted at 2050℃ to form a sleeve rod with an outer diameter of 35mm; the highly doped preform is fitted into a high-purity B2O3 sleeve with a suitable inner hole to obtain the cladding modified preform. The remaining steps and process parameters are the same as those in embodiment 1.

[0053] Comparative Example 1: Please see Figure 4 Comparative Example 1 provides a ytterbium-doped ordinary optical fiber, whose cross-sectional structure is consistent with that of conventional optical fiber, including Yb doping. 3+ The fiber core 10 and cladding 20 are different in that: in step (6), stress layer 30 is not introduced. Instead, a high-purity quartz sleeve is matched according to a core-to-cladding ratio of 0.08 and melted at 2050℃ to form a sleeve rod with an outer diameter of 35mm. The remaining steps and process parameters are the same as in Example 1.

[0054] Results and Analysis: The refractive index parameters of Examples 1, 2, 3 and Comparative Example 1 after a high-temperature wire drawing and rapid cooling process were actually measured, and the results are shown in Table 1: Table 1. Refractive index changes of Examples 1 to 3 and Comparative Example 1 after high-temperature wire drawing and rapid cooling process.

[0055] As shown in Table 1, in Examples 1, 2, and 3, the core refractive index decreased to varying degrees after high-temperature drawing and rapid cooling by introducing stress layers 30 at different positions of the cladding 20. In contrast, in Comparative Example 1, which did not undergo cladding modification, the core refractive index showed no significant change. These results indicate that the cladding-modified optical fiber fabrication method provided by this invention can effectively reduce the core refractive index through the tensile stress generated by the stress layer 30 during rapid cooling. In the examples employing a continuous annular structure stress layer 30, Example 1, where the stress layer 30 is closely attached to the core 10, exhibits a more significant refractive index reduction effect compared to Example 3, where the stress layer 30 is located on the outer surface of the cladding 20. Furthermore, the continuous annular structure stress layer 30 generates a more uniform and significant circumferential stress effect compared to discretely distributed stress units 31, thus achieving a more pronounced refractive index reduction effect.

[0056] Unlike existing technologies, the cladding-modified optical fiber and its preparation method provided by this invention have the following advantages: (1) This invention further reduces the refractive index of the fiber core by modifying the cladding 20 without changing the doping formula of the fiber core 10, breaks through the upper limit of the fluorine doping concentration of the fiber core 10, increases the relative refractive index difference between the fiber core 10 and the cladding 20, and reduces bending loss; at the same time, it does not reduce the solubility of rare earth ions, has no ion quenching problem, and has higher laser gain per unit length.

[0057] (2) This invention utilizes the difference in thermal expansion coefficient between the high thermal expansion coefficient material and the pure quartz matrix. After high-temperature drawing, the stress layer 30 is rapidly cooled to cause it to shrink sharply, generating uniform outward radial tensile stress on the fiber core 10. By means of the quartz elastic-optical effect, the refractive index of the fiber core is linearly reduced. This is a purely physical control method and does not require the introduction of additional doping elements.

[0058] (3) In this invention, the stress layer 30 is centrally symmetrically distributed about the central axis of the fiber core 10, and the resulting tensile stress is uniform and consistent along the circumference, and only uniformly lowers the refractive index of the bulk fiber core; unlike the scheme of the panda polarization-maintaining fiber which squeezes the fiber core 10 inward to generate anisotropic compressive stress and thus form birefringence, this invention does not induce polarization birefringence, and the beam circular symmetry and polarization stability are good.

[0059] (4) The present invention processes the optical fiber preform by means of cladding modification without disturbing the core doping region. It can be adapted to the existing mainstream commercial optical fiber preform production methods (such as MCVD process). The stress is formed naturally during the rapid cooling stage of fiber drawing, without the need for additional heat treatment steps. The process is simple, low cost and easy to mass produce.

[0060] It should be noted that all the above embodiments belong to the same inventive concept, and the descriptions of each embodiment have different focuses. Where the description in a particular embodiment is not detailed, please refer to the description in other embodiments.

[0061] The above embodiments merely illustrate implementation methods of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.

Claims

1. A cladding-modified optical fiber, characterized in that, It includes a fiber core and a cladding arranged radially from the inside to the outside, wherein the refractive index of the fiber core is greater than the refractive index of the cladding; The cladding modified optical fiber further includes a stress layer disposed radially on the outside of the fiber core, the stress layer being used to reduce the refractive index of the fiber core by generating stress.

2. The cladding-modified optical fiber according to claim 1, characterized in that, The stress layer is centrally symmetrical about the central axis of the fiber core; and / or, the relative refractive index difference between the stress layer and the cladding is -0.5% to +0.5%.

3. The cladding-modified optical fiber according to claim 1, characterized in that, The stress layer is a continuous annular structure that completely encloses the fiber core, or it is a plurality of stress units that are spaced apart circumferentially on the outside of the fiber core. Wherein, when the stress layer is the continuous annular structure, the continuous annular structure is disposed on the outer surface side of the fiber core or the outer surface side of the cladding; when the stress layer is a plurality of stress units, the plurality of stress units are embedded in the radial center of the cladding.

4. The cladding-modified optical fiber according to claim 3, characterized in that, When the stress layer is disposed on the outer surface of the fiber core and the numerical aperture of the fiber core is ≥0.10, the stress layer is formed of a first stress material; when the stress layer is disposed on the outer surface of the fiber core and the numerical aperture of the fiber core is <0.10, the stress layer is formed of a second stress material; when the stress layer is disposed in the radial center of the cladding or on the outer surface of the cladding, the stress layer is formed of the first stress material. Wherein, the relative refractive index difference of the first stress material relative to the cladding is negative, and its coefficient of thermal expansion is greater than that of the cladding; the relative refractive index difference of the second stress material relative to the cladding is positive, and its coefficient of thermal expansion is greater than that of the cladding.

5. The cladding-modified optical fiber according to claim 1, characterized in that, The diameter of the fiber core is 4 to 100 μm; and / or the material of the stress layer includes at least one of B2O3, TiO2 and alkali metal oxides; and / or the absolute refractive index of the fiber core is reduced by not less than 0.0003 compared with the absolute refractive index of the fiber core without the stress layer.

6. A method for preparing a cladding-modified optical fiber according to any one of claims 1 to 5, characterized in that, include: S10, a clean quartz tube is placed on a lathe, a first mixed gas is introduced into the quartz tube, and a fluorine-containing barrier layer is deposited on the inner wall of the quartz tube to obtain a first reaction tube; the first mixed gas includes oxygen, silicon tetrachloride and sulfur hexafluoride. S20, a second mixed gas is introduced into the first reaction tube, and a loose layer is deposited on the tube wall of the first reaction tube to obtain a second reaction tube; the second mixed gas includes oxygen, helium, silicon tetrachloride and germanium tetrachloride; S30, the second reaction tube is subjected to vitrification shrinkage treatment at 1800-2100℃ to shrink it into a solid rod, thus obtaining a fiber core preform rod; S40, the fiber core preform is processed into a core rod to form the stress layer at any one of the following locations: the outer surface of the fiber core, the radial center of the cladding, or the outer surface of the cladding, thereby obtaining a cladding modified preform. S50, the cladding modified preform is subjected to high-temperature melting and drawing at 2000-2200℃ to obtain the cladding modified optical fiber.

7. The preparation method according to claim 6, characterized in that, After step S20 and before step S30, the following steps are also included: The second reaction tube is immersed in a first ion solution containing rare earth ions; The second reaction tube, after soaking, is baked under a third mixed gas to obtain a first dry reaction tube; the third mixed gas includes silicon tetrachloride, oxygen, helium and chlorine.

8. The preparation method according to claim 7, characterized in that, The solvent of the first ionic solution is pure water or anhydrous ethanol, the solute contains at least one rare earth ion with a concentration of 0.03–0.2 mol / L, and the soaking time is 0.5–2 h; and / or, The flow rate of silicon tetrachloride in the third mixed gas is greater than 180 sccm and less than or equal to 300 sccm, and the flow rate of chlorine is greater than 100 sccm and less than or equal to 200 sccm; and / or, The second reaction tube is baked using an oxyhydrogen lamp at a temperature of 800–1400°C, with the lamp moving in the same direction as the flow of the third mixed gas within the second reaction tube.

9. The preparation method according to claim 6, characterized in that, The S40 step specifically includes: removing the cladding of the fiber core preform and taking out the fiber core; sequentially matching the first stress modification component and the first quartz sleeve according to a preset core-cladding ratio; and sequentially performing high-temperature melting and shrinking at 2000–2100°C; or, The fiber core preform is subjected to size testing. The second quartz sleeve is matched according to the preset core-to-pack ratio and melted at high temperature of 2000-2100℃. The melted first rod is inserted into the third quartz sleeve. Holes are drilled in the third quartz sleeve at positions symmetrical to the center of the fiber core, and at least two second stress-modifying components are inserted and melted at high temperature of 2000-2100℃. Alternatively, the fiber core preform is subjected to dimensional testing, a fourth quartz sleeve is matched according to a preset core-to-wall ratio, and the core is melted and shrunk at a high temperature of 2000-2100°C. The shrunk second rod is then fitted into the second stress-modified component.

10. The preparation method according to claim 9, characterized in that, The first stress-modifying component is a TiO2 sleeve with a refractive index lower than that of the fiber core; and / or, the second stress-modifying component is a boron rod or a B2O3 sleeve, wherein the molar concentration of B2O3 in the boron rod is 10 mol% to 30 mol.